2021
DOI: 10.1111/hsc.13521
|View full text |Cite
|
Sign up to set email alerts
|

Unmet dental care needs of homeless adults in South Korea: Findings from a national survey

Abstract: This study identifies the key factors underlying the unmet dental care needs of South Korean homeless adults that obstructed their dental service access. We analysed data from 551 Korea Homeless Survey respondents (17 years and older) who reported having an oral disease in the previous 12 months. We conducted multiple logistic regression analyses to examine the factors associated with homeless individuals’ unmet dental care needs, using weights to make the data nationally representative. Approximately 43% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…These results are inconsistent with previous studies that reported economic hardship to be the primary concern among adults, particularly MA recipients. 24 , 25 MA is a government-funded system for providing healthcare benefits for low-income families who cannot pay the premium to NHI but desperately need medical care. Consequently, the UMNs of certain economically vulnerable groups are significantly more affected by finances such as income; therefore, there is a high probability of high rates of UMN before the pandemic but not during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…These results are inconsistent with previous studies that reported economic hardship to be the primary concern among adults, particularly MA recipients. 24 , 25 MA is a government-funded system for providing healthcare benefits for low-income families who cannot pay the premium to NHI but desperately need medical care. Consequently, the UMNs of certain economically vulnerable groups are significantly more affected by finances such as income; therefore, there is a high probability of high rates of UMN before the pandemic but not during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…미충족 치과의료를 경험하는 집단의 규모와 그 원인을 파악하는 것은 치과의료 접근성을 강화하는 데 도움이 될 뿐만 아니라 10) 실효성 있는 보건의료정책을 수립하는 데 매우 유용하다 11) . 기존 선행연구에 서 밝혀진 미충족 치과의료에 영향을 미치는 관련 요인은 인구학적 특 성(성별, 연령), 사회경제적 특성(고용상태, 교육수준, 혼인상태, 소득 수준), 건강 관련 특성(주관적 구강건강상태, 저작불편 유무, 주관적 스 트레스) 등이었다 8,[10][11][12][13][14][15][16] . 보건의료 취약계층과 관련하여 Che 등 15) 12,15,16) , 임신부를 대상으로 한 관련 국외 연구는 활발히 진행되었 음을 확인하였다 13,21) .…”
unclassified
“…기존 선행연구에 서 밝혀진 미충족 치과의료에 영향을 미치는 관련 요인은 인구학적 특 성(성별, 연령), 사회경제적 특성(고용상태, 교육수준, 혼인상태, 소득 수준), 건강 관련 특성(주관적 구강건강상태, 저작불편 유무, 주관적 스 트레스) 등이었다 8,[10][11][12][13][14][15][16] . 보건의료 취약계층과 관련하여 Che 등 15) 12,15,16) , 임신부를 대상으로 한 관련 국외 연구는 활발히 진행되었 음을 확인하였다 13,21) . 국내의 경우 임산부의 구강건강에 대한 인지도 및 실천도를 파악하기 위해 임신 중 치과 치료와 구강보건교육 경험 현황을 살펴본 연구는 다수 존재하였으나 6,7)…”
unclassified